2014
DOI: 10.1177/0961203314527366
|View full text |Cite
|
Sign up to set email alerts
|

Chinese SLE Treatment and Research group (CSTAR) registry: II. Prevalence and risk factors of pulmonary arterial hypertension in Chinese patients with systemic lupus erythematosus

Abstract: The possible prevalence of PAH was 3.8% in Chinese patients with SLE in the CSTAR registry. The significant association of pericarditis, pleuritis and anti-RNP positivity with PAH suggests that higher disease activity and vasculopathy may both contribute to the development of PAH in SLE, which need be treated aggressively to improve prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
81
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(91 citation statements)
references
References 43 publications
6
81
4
Order By: Relevance
“…13,3640 Data based on CSTAR has shown pericardial effusion, serositis, and anti-RNP antibody are independent risk factors in ECHO-based SLE-PAH patients, 19 and later analysis of auto-antibodies has found that there is relevance between anti-SSA antibody and PAH. 41 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…13,3640 Data based on CSTAR has shown pericardial effusion, serositis, and anti-RNP antibody are independent risk factors in ECHO-based SLE-PAH patients, 19 and later analysis of auto-antibodies has found that there is relevance between anti-SSA antibody and PAH. 41 …”
Section: Discussionmentioning
confidence: 99%
“…This group mimics SSc-PAH, in which irreversible vascular pathological changes, especially proliferation of endothelial cells and vascular smooth muscle cells, gradually lead to PAH during long disease duration. Anti-RNP antibody and Raynaud's phenomenon (RP) were believed to be associated with this subtype, 14,19,34,42 and RP was also proved as an indicator of disease severity. 36,38,42–44 Percentage of RP in our study was 64.5%, in accordance with previous published data; 45 however, we lack the data of the control group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2). Based on the SLE patients registered in the CRDC, papers on basic demographic characteristics and first symptom in Chinese SLE patients [5], risk factors of pulmonary hypertension [8], correlations between autoantibodies and clinical manifestations [9], and factors related to fetal loss [10] have been published. The SLE patients in the study of Li et al showed differing primary symptoms [5], of which rash, arthritis, fever, cytopenia, and kidney disease were the most common.…”
Section: Resultsmentioning
confidence: 99%
“…However, most patients in that study had overt right heart failure, which may have contributed to pleural effusion. In a recent analysis of a large Chinese cohort (n=1,934, 74 patients with PAH), pleuritis was an independent predictor of PAH in lupus and showed an odds ratio (OR) =3.06 (95% confidence interval [CI] =1.6–5.85) 18. Additional clinical manifestations with an independent predictive ability for PAH were interstitial lung disease (OR =17, 95% CI =3.6–80) and pericardial effusion (OR =21.3, 95% CI =4.1–110.6) 13.…”
Section: Predictive Factorsmentioning
confidence: 99%